Social groups and children‟s intergroup prejudice: Just how influential are social group norms? - Nesdale, Drew (Anales de Psicología / Annals of Psychology, 2011)
Drawing upon social identity development theory (SIDT, Nesdale, 2007), a series of research studies examined the impact of social group norms on group members‟ intergroup prejudice. Studies 1-3 on pre-schoolers to 9-year olds showed that an ingroup norm of exclusion instigated outgroup dislike in ingroup members whereas an inclusion norm prompted outgroup liking. Studies 4 and 5 showed that as children increase in age during the middle childhood period, they display less and less liking for ingroup members who display traits and behaviours that are inconsistent with those expected from ingroup members. Studies 6 and 7 examined several factors that might be expected to extinguish or, at least, moderate young children‟s negative outgroup attitudes. However, whereas children‟s empathy was found not to moderate an ingroup exclusion norm, the latter was moderated by a school norm of inclusion. The findings are discussed in relation to SIDT, and possible strategies for moderating the effects of group norms.